PENGARUH MEDIA SOSIAL TERHADAP SITASI PUBLIKASI INTERNASIONAL KARYA ILMIAH INDONESIA BIDANG PERTANIAN DENGAN PENDEKATAN ALTMETRICS - Ibrahim, Cecep; Sukaesih Sitanggang, Imas; Sukoco, Heru (BACA: Jurnal Dokumentasi dan Informasi, 2025)
The purpose of this study was to measure the impact of Indonesia research especially in agriculture published in international Scopus journals using Altmetrics. This research method consisted of problem identification, data collection, data preprocessing, Altmetrics approach analysis, and final analysis. The data of this study were obtained from Scopus.com citation metadata by writing the Agriculture keyword and Indonesian affiliation that the limited year from 2015-2017. Altmetrics data is obtained from Altmetric.com; Altmetrics Explorer for Librarian by extracting DOIs from each publication of scientific work. Then the data is analyzed by the Altmetrics approach, namely Facebook Coverage and Mention Rate. This study performed an analysis based on Altmetrics data share to know the popularity Indonesian research in Scopus journal and analyzed the correlation between Citation data Indonesian research in Scopus journal and Altmetrics data share of Altmetric.com. This study analyzed the impact of 4484 Indonesia research articles published by Scopus journals in the field of agriculture through Altmetrics and compared it with bibliometrics. The result showed that Coverage and Mention Rate of social media only were below 30% which was not too significant in the content discussed, view & reader and mention on social media.